The Authority Analysis of Non-Legal Entity Organization and Opportunities for Dispute Resolution Through Litigation - Sufiarina, Sufiarina; Alias, Nizamuddin; Sopyan, Yayan; Enijaya, Enijaya (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2024)
Article 28 of the Indonesian Constitution is formulated to guarantee the freedom of associations and assembly, including the formation of community organizations (ormas). Ormas holding legal entity status are accommodated under associations, while non-legal entity ormas can still register but do not have the same status. The distinction between ormas and associations lies in their legal recognition. Associations possess legal entity status, while ormas are considered non-legal entities. According to Article 20 of Law No. 17 of 2013, ormas have the right to cooperate with other entities to develop and sustain their organizations. However, such cooperation may give rise to conflict, which cannot always be avoided. This raises important questions, such as